The Effectiveness of Training Reality Therapy Concepts on the Happiness of Elder People - Kazem Khazan; Seyed Jalal Younesi; Mahshid Foroughan; Heiman Saadati (University of Social Welfare & Rehabilitation Sciences, 2015)
Objectives: The aim of this study was to examine the effectiveness of reality therapy on the happiness of the elderly people. Methods & Materials: This is an experimental study with a pretest posttest design and a control group. Sample of the study selected from the elderly members of Mandegaran Club in Ardebil City. All who were over 50 years were evaluated according to inclusion/exclusion criteria and 30 participants selected and randomly divided into 2 equal groups. Oxford happiness scale was administered to both groups. Reality therapy sessions for the intervention group were administered in 80-minute sessions, 2 sessions per week for 4 successive weeks. The posttest data collected after the last session and also doing a follow up one month later. Data analyzed by using analysis of variance with repeated measure for independent groups. Results: Results of analysis of variance showed that the mean difference between the two groups were significant (P<0.05) and reality therapy increased the happiness of intervention group significantly. Happiness scores of intervention group in all subscales were also significantly higher in posttest compared to control group (P<0.001). Conclusion: The results showed that reality therapy can be helpful in enhancing positive emotions and happiness in older people. Implementation of reality therapy sessions in nursing homes, and retirement centers are recommended.